“ENTRÉE INTO THE MIND AND MOOD OF AMERICA”: PROVERBS IN COMMENCEMENT RHETORIC - Konstantinova, Anna (Proverbium - Yearbook, 2018)
The present paper explores different aspects of proverb use in the commencement address discourse. It draws on the analysis of 100 speeches delivered at US universities over the past three decades. First, I offer some introductory remarks about the commencement ceremony as a socio-cultural phenomenon. Second, I look at the discursive characteristics of the commencement address. Next, I analyze the role proverbs play on the thematic level of the speeches and provide comments on their cognitive-discursive functions in the most significant thematic groups distinguished in the course of study. Last, I offer a closer study of the entertaining function and the function of structural organization of discourse proverbs fulfill in the commencement address.